Identifikasi Tingkat Kematangan Gonad Kerang Darah (Anadara Granosa) Di Panipahan, Kabupaten Rokan Hilir, Provinsi Riau - Riza, Subkhan; Putra, Iskandar; Suprijanto, Jusup; Widowati, Ita (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2024)
Riau Province needs to develop blood cockle (Anadara granosa) of seeding technology as an effort to reduce dependence on natural capture and dependence on seeds for cultivation from nature, which can threaten the sustainability of these biota resources. This research aims to determine the growth in length, weight and condition index of blood clams, and determine the gonad maturity level (TKG) of blood cockle. Length growth analysis (morphometric) in August 2019 with size classes small, medium to large and there was an increase in October 2019 in average size to medium to large. The results of the weight growth analysis (biometric) in August 2019 showed a value of b= 1.8903 and in October 2019 a value of b= 2.1382 indicating negative allometry. Where the increase in length is faster than the increase in weight. The gonads have developed well because they have reached a condition index > 20.00. The results of macroscopic analysis showed that blood cockle samples could be distinguished between male gamete cells and female gamete cells based on the color and shape of the gonads. Based on macroscopic and histological analysis, it shows that the level of gonad maturity is thought to have reached stage II (developing) in the developing stage. By knowing the gonad maturity level of the blood cockle, it is hoped that it can be implemented in supporting the construction of a blood cockle hatchery unit in Riau Province.